Hypothalamic-Pituitary Axis Regulates Hydrogen Sulfide Production - Hine, Christopher (Cell Metab, 2017)
Decreased growth hormone (GH) and thyroid hormone (TH) signaling are associated with longevity and metabolic fitness. The mechanisms underlying these benefits are poorly understood, but may overlap with those of dietary restriction (DR), which imparts similar benefits. Recently we discovered that hydrogen sulfide (H(2)S) is increased upon DR and plays an essential role in mediating DR benefits across evolutionary boundaries. Here we found increased hepatic H(2)S production in long-lived mouse strains of reduced GH and/or TH action, and in a cell-autonomous manner upon serum withdrawal in vitro. Negative regulation of hepatic H(2)S production by GH and TH was additive and occurred via distinct mechanisms, namely direct transcriptional repression of the H(2)S-producing enzyme cystathionine γ-lyase (CGL) by TH, and substrate-level control of H(2)S production by GH. Mice lacking CGL failed to downregulate systemic T(4) metabolism and circulating IGF-1, revealing an essential role for H(2)S in the regulation of key longevity-associated hormones.